Patho-physiological investigation of anorexia of cattle at Sylhet district in Bangladesh (International Journal of Natural Sciences, 2016)
The present study was designed to explore the patho-physiological investigation of anorexia of cattle at Sylhet district, Bangladesh. The aim of this study has been conducted to determine the patho-physiological causes of anorexia in cattle during the study period started from September to December in Bishwanath upazila veterinary hospital, Sylhet. Anorexia is one of the most common illness among female cattle in Bangladesh. In this study, a total number of 155 diseased cattle, 100 cattle were found having anorexia due to parasitic, infectious, nutritional deficiency and unknown etiology. Results of this study showed most anorexia developed due to parasitic infestation (41%) which was determined by feces examination and observing the body condition of the animal. The female cattle developed anorexia in higher rate (67%). The early age (less than 1year) of the cattle were found mostly to develop anorexia in cattle, may be due to parasitic and nutritional deficiencies cause.International Journal of Natural Sciences (2015), 5(2) 90-92